EVALUASI TANAH PENUTUP PERTAMBANGAN BATUBARA CV. INTAN KARYA MANDIRI, DI KABUPATEN BANJAR, PROVINSI KALIMANTAN SELATAN - Jauhari, Rijal; Mahyudin, Idiannor; Lilimantik, Emmy; Hafizianor, Hafizianor (EnviroScienteae, 2023)
Coal mining activities using the open pit mining method can affect depreciation of the quality of the surrounding environment, one of which has an impact on reducing the classification criteria for soil chemical properties. The soil organic matter shrinks after being mined due to the lifting of the top layer due to the dismantling of the coal covering material. The research objective is to analyze the effect of mining activities on soil classification in the disposal area. The research method is descriptive analysis. Sampling and observation in Cintapuri Village, Cintapuri Darussalam District, Banjar Regency. Soil classification in Disposal 1, soil pH is classified as "Very Acid" to "Sour", C-organic is classified as "Very Low", N-Total is classified as "Very Low" to "Low", phosphorus is classified as "Very Low", Cation-exchange capacity (CEC) is classified as "moderate". Disposal 2, Soil pH is classified as "acid", C-organic is classified as "Very Low", N-Total is classified as "Very Low" to "Very Low", phosphorus is classified as "Very Low", CEC is classified as "Medium" and "High". Based on the research, the existence of coal mining activities causes the chemical properties of the soil in the disposal area as low criteria.